USM SETS SIGHT ON ACTIVE ENGAGEMENT BETWEEN ACADEMIA AND INDUSTRY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, April 2015 Universiti Sains Malaysia (USM) aims to have 40 percent of more than its 2,000 academicians to be involved in active and consistent collaboration with the industry within the next three years. The USM ViceChancellor Professor Dato’ Dr. Omar Osman said, at present USM has in its record of more than 800 of its academicians and 1,000 nonacademic staff involved in close collaboration with various industries and communities.